Associated factors, emergency department visits, and hospitalization days of receiving adjunctive Chinese herbal medicine therapy for patients with non-small cell lung cancer: a nationwide cohort study in Taiwan - Tang, Meng-Bin; Kuo, Wei-Yin; Kung, Pei-Tseng; Tsai, Wen-Chen (Frontiers in Pharmacology, 2025)
IntroductionCancer prevention and treatment, particularly lung cancer, remain major healthcare challenges in Taiwan and globally. This study investigates factors and healthcare utilization patterns associated with adjunctive Chinese herbal medicine (CHM) therapy in non-small cell lung cancer (NSCLC) patients.MethodsUsing Taiwan’s National Health Insurance Research Database and the Taiwan Cancer Registry, we conducted a retrospective cohort study of non-small cell lung cancer patients diagnosed between 2007 and 2013. Descriptive analysis, propensity score matching, and regression models were employed to assess CHM therapy utilization and its impact on emergency department visits and hospitalization days.ResultsAmong 43,122 non-small cell lung cancer patients, 5.76% received adjunctive CHM therapy, with the majority at stage IV cancer. Factors such as cancer stage, age, gender, marital status, education level, monthly salary, degree of urbanization, severity of comorbidity, comorbid diseases, hospital ownership, experience of using Chinese medicine, chemotherapy status, and years of diagnosis are significantly associated with whether NSCLC patients receive adjunctive CHM therapy. Patients receiving adjunctive CHM therapy for 181–365 days reduced emergency department visits by 16% (OR = 0.84, 95%CI: 0.74-0.95) and shortened hospitalization days by 17% (Ratio = 0.83, 95%CI: 0.75-0.91).ConclusionProlonged adjunctive CHM therapy, particularly for 181–365 days, is associated with decreased healthcare utilization among non-small cell lung cancer patients. These findings suggest a potential role for extended CHM therapy in managing NSCLC and warrant consideration by clinical teams.